2011
DOI: 10.1111/j.1447-0756.2010.01490.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anti‐β2‐glycoprotein I antibody on PlGF, VEGF and sVEGFR1 production from cultured choriocarcinoma cell line

Abstract: Anti-β2-GPI antibody-positive sera and IgG suppress the production of PlGF from JEG-3 cells. We suggest that the anti-β2-GPI antibodies may suppress PlGF production from trophoblasts and cause the failure of placenta formation and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
(34 reference statements)
0
6
0
1
Order By: Relevance
“…A study by Di Simone and co-workers suggested that one of the causes of aPL-mediated foetal loss was inhibition of angiogenic factor secretion and direct impairment of the placenta angiogenesis [25]. The possible effects of aPLs include limiting trophoblast migration [26], suppressing placenta growth factor production [27] and also modulation of trophoblast angiogenic factor secretion [28].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Di Simone and co-workers suggested that one of the causes of aPL-mediated foetal loss was inhibition of angiogenic factor secretion and direct impairment of the placenta angiogenesis [25]. The possible effects of aPLs include limiting trophoblast migration [26], suppressing placenta growth factor production [27] and also modulation of trophoblast angiogenic factor secretion [28].…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8]30 The major pathogenic mechanisms of adverse pregnancies caused by anti-phospholipid antibodies are a hyperthrombogenic state in the intervillous space due to the damage of endothelial cells caused by anti-phospholipid antibodies, 17 as well as direct damage to chorionic villi during the period of placentation. [13][14][15][16] Taking account of these mechanisms, immunosuppressive therapy in combination with anti-coagulation therapy should be adopted as a treatment option for patients with adverse pregnancies caused by anti-phospholipid antibodies. In fact, some authors pointed out the insufficient efficacy of heparin therapy for such patients.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] As an alternative treatment, the efficacy of combined therapy using adrenal corticosteroid hormone (prednisolone) and low-dose aspirin was initially reported. 12 The major pathogenic mechanisms leading to the diversity of adverse pregnancies are considered to be direct damage to chorionic villi by anti-phospholipid antibodies, [13][14][15][16] as well as the formation of intervillous thrombi. 17 Taking account of these mechanisms for reproductive failures caused by anti-phospholipid antibodies, the application of immunosuppressive therapy in combination with anti-coagulation therapy should be reconsidered as a treatment option.…”
Section: Introductionmentioning
confidence: 99%
“…The main mechanisms involved in the generation of reproductive failures are considered to be the occurrence of direct damage to the chorionic villi caused by antiphospholipid antibodies during the period of placentation [15][16][17][18], and the formation of thrombi intervillous spaces [19]. Considering these mechanisms, the administration of immune suppressive therapy in combination with anti-coagulation therapy is considered to be a viable treatment option.…”
Section: Discussionmentioning
confidence: 99%